Russian - Ottoman Relations: During the Reign of Czar Peter the Great 1682-1725 - Abdullah, Nagham Talib (Al-Adab Journal, 2020)
The Russian-Ottoman Relations occupied a great deal of interest in the History of International Relations in the Sixteenth and Seventeenth Centuries، due to their logistic importance in the episodes of the conflict within the Eastern Question، which accompanied the diminishing power of the Ottoman Empire and the raised of the European powers greed to divide their possessions in Europe، Asia and Africa. Under the reign of Czar Peter the Great، Russia played a pivotal role in that conflict، in response to the supreme goals of the Romanov Czars، to break the isolation imposed by Geography and Climate on their Country، and to reach the Warm، Navigable waters، To keep up with the wheel of Evolution and Modernization adopted by Peter during his Reign 1682-1725.